Never kiss a notorious marquess - Miller, Renee Ann (Miller, Renee Ann. Infamous lords series., 2019)
For James Trent, Lord Huntington, there<U+2019>s no escaping the question that labeled him The Murdering Marquess: was his wife<U+2019>s death a tragic accident or a cold-blooded crime? He<U+2019>s avoided London<U+2019>s gossipmongers since that terrible night, as guardian to his younger siblings on his Essex estate. But trouble finds him when a veiled temptress with secrets of her own falls<U+2014>quite literally<U+2014>into his arms. Caroline Lawrence doesn<U+2019>t need a man to rescue her<U+2014>the aspiring journalist anonymously advocates for women<U+2019>s rights in a radical London newspaper column. But when a suffragist<U+2019>s soapbox speech turns to pandemonium, Caroline is knocked on the head and reawakens in Trent Hall<U+2014>with the notorious lord of the manor irresistibly close. If there is any truth to his tarnished past, she should denounce him with her powerful pen. Yet love has a way of revealing a man<U+2019>s true character . . .